2000
DOI: 10.3354/meps204027
|View full text |Cite
|
Sign up to set email alerts
|

Marine microbenthic community structure regulated by nitrogen loading and grazing pressure

Abstract: Generalisations on the combined effects of consumers and resources on autotrophs in aquatic food webs largely rely on freshwater studies. In this study, we tested these general concepts with marine benthic microalgae, which are important components of coastal food webs. We manipulated nitrogen availability and herbivore presence in a factorial field experiment in the Western Baltic Sea. Moreover, we investigated how herbivore control varied among 3 sites and 2 seasons and tested for trophic cascades by enhanci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
145
1
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 159 publications
(165 citation statements)
references
References 55 publications
14
145
1
5
Order By: Relevance
“…These findings are in agreement with previous studies on benthic diatoms from marine (e.g., Hillebrand et al 2000), and freshwater (Steinman 1996;Hill et al 1997), habitats. In our study, the absence of grazers generally favoured the abundance of the diatom genus Cocconeis.…”
Section: Grazing Effectssupporting
confidence: 94%
See 2 more Smart Citations
“…These findings are in agreement with previous studies on benthic diatoms from marine (e.g., Hillebrand et al 2000), and freshwater (Steinman 1996;Hill et al 1997), habitats. In our study, the absence of grazers generally favoured the abundance of the diatom genus Cocconeis.…”
Section: Grazing Effectssupporting
confidence: 94%
“…In our experiment, as observed by others (e.g., Hillebrand et al 2000), some inconsistent cage artefacts were found; a higher biomass but a lower abundance in half cages compared with open ones at the second and forth sampling, respectively. These findings are most likely a consequence of the high natural variability in these types of fieldexperiments.…”
Section: Methodological Considerationssupporting
confidence: 88%
See 1 more Smart Citation
“…However, species optimizing one functional trait commonly have to pay costs regarding other traits due to physiological, energetic, and genetic constraints (Stearns, 1989). Trade‐offs between defense and competitiveness have been frequently found in nature and may explain the high diversity of strategies along the gradient of being defended or highly competitive (Agrawal, 1998; Coley, Bryant, & Chapin, 1985; Hillebrand, Worm, & Lotze, 2000). Predation may enable coexistence of competing species facing a trade‐off between defense and competitiveness.…”
Section: Introductionmentioning
confidence: 99%
“…A decrease in cell number of microphytobenthic or epiphytic communities in the presence of invertebrate grazers is a well-known phenomenon which has been detected in numerous studies (Sommer 1997;Hillebrand et al 2000;Schanz et al 2002;Jaschinski et al 2008). In our experiment, both algal species were grazed to a similar degree by the studied grazers indicating that no active choice of food components took place.…”
Section: Algal Biovolumementioning
confidence: 93%